Evolutionary algorithms - Edelmann-Nusser, J. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
The focus of this chapter is on Evolutionary Algorithms, which have a wide variety of applications in sports and sports science. Their application is useful when a target variable depends on a large number of parameters (such as competition performance on many different training contents of the previous weeks). The procedure of an Evolutionary Algorithm can be described as follows: